PENGARUH REKLAMASI PANTAI TERHADAP KONDISI SOSIAL EKONOMI NELAYAN (STUDI KASUS KELOMPOK NELAYAN DI KAWASAN MEGAMAS) - TUMBEL, HEGEL; DENGO, SALMIN; KOLONDAM, HELLY (JURNAL ADMINISTRASI PUBLIK, 2019)
The aim of the research is to measure the impact of coastal reclamation on the social and economiccondition of fishermen in Sario Tumpaan. This research uses quantitative approach methods. The subjectof this study amounted to 30 of one group occupying the research site so that researchers took theconclusion to give Kuisoner to the 30 subjects. Data collection uses questionnaires and interviews, whilethe analytical techniques used are validity and reliability tests as well as the homogeneous test modelGhozali, 2011. Based on the results of the research that has been done by the authors, it can be concludedas follows: (1) based on the results of research that has been tested from some data with a population of 1organization and there are 30 people who are respondents. The Data obtained is declared valid or normaldistribution so it is feasible to proceed with a simple linear regression analysis test. (2) The socialeconomic erdahap of the fishermen of the city of Manado Mega Mas has been carried out quite well, it isseen from the results of the research scoring instrument that puts the reclamation variable to be in thecategory quite good until good. (3) reclamation has a positive and significant relationship and influenceon the social economy of the fishermen Mega City of Manado, which means the reclamation variable is afactor that determines the determinant of the socio-economic fishermen. The more Basar reclamation thatis done the greater also impacts on the social economy of fishermen of the Mega district Mas CityManado.Keywords: Reclamation, Social, Economic, Fishermen